ChemInform Abstract: The Preparation of Various New Heterocyclic Compounds via Cyclization of Substituted Derivatives of Phenacyl Esters of Hydrazonoacetic Acid. Issue 6 (11th February 2014) - Melnicky, Radek; Grepl, Martin; Lycka, Antonin; Bertolasi, Valerio; Kvapil, Lubomir; Dvorakova, Barbora; Hradil, Pavel
Abstract The acid‐mediated Fischer‐indole synthesis type cyclization of hydrazones (I) and (V) is studied resulting in the formation of indoles (II) and (VI).